(untitled) (Yearbook - Faculty of Economics, 2013)
Value chain in todays global marketing management is seen as a group of vertically aligned organizations that add value to a good or service in moving from basic supplies to finished products for consumer and organizational end users. Strategic choices in value chain options are an important part of marketled strategy. The term value chain focuses attention on the processes, activities, organizations, and structures that combine to create value for customers as products move from their point of origin to the end user. The value chain network is the configuration of distribution channels linking value-chain members with end users. Channels of distribution are a central issue in managing the value chain. An effective and efficient distribution channel provides the member organizations with an important strategic edge over competing channels. Also, there is a need for marketing decision makers to incorporate into their thinking the impact of innovations in supply chain strategy. The important goal is maintaining the ability of the market-driven company to realign its value chain when this is necessary to meet the changing needs of its customers and markets. The paper is formulating the value chain strategy by focusing at the role of distribution channels in marketing strategy and discuss several channel strategy issues; the process of selecting the type of channel; determining the intensity of distibution; choosing the channel configuration of organizations; managing the distribution channel; distributing through international channels and supply chain management issues.